The carotenoid fucoxanthin can sensitize multidrug resistant cancer cells to doxorubicin via induction of apoptosis, inhibition of multidrug resistance proteins and metabolic enzymes - Eid, Safaa Yehia; Althubiti, Mohammad Ahmad; Abdallah, Mohamed E.; Wink, Michael; Readi, Mahmoud Zaki el (Phytomedicine, 2020)
Background - Multidrug resistance (MDR) causes failure of doxorubicin therapy of cancer cells, which develops after or during doxorubicin treatment resulting in cross-resistance to structurally and functionally-unrelated other anticancer drugs. MDR is multifactorial phenomenon associated with overexpression of ATP-binding cassette (ABC) transporters, metabolic enzymes, impairment of apoptosis, and alteration of cell cycle checkpoints. The cancer-prevention of the dietary carotenoid; fucoxanthin (FUC) has been extensively explored. Nevertheless, the underlying mechanism of its action is not full elucidated. - Hypothesis/Purpose - Investigation of the underlying mechanism of MDR reversal by the dietary carotenoid fucoxanthin (FUC) and its ability to enhance the doxorubicin (DOX) cytotoxicity in resistant breast (MCF-7/ADR), hepatic (HepG-2/ADR), and ovarian (SKOV-3/ADR) cell lines. - Methods - The synergistic interaction of FUC and DOX was evaluated using several techniques, viz.; MTT assay, ABC transporter function assays using FACS and fluorimetry, enzyme activity via spectroscopy and luminescence assays, and apoptosis assay using FACS, and gene expression using RTPCR. - Results - FUC (20 µM) synergistically enhanced the cytotoxicity of DOX and significantly reduced the dose of DOX (FR) in DOX resistant cells (MCF-7/ADR), hepatic (HepG-2/ADR), and ovarian (SKOV-3/ADR) to 8.42-(CI= 0.25), 6.28-(CI= 0.32), and 4.56-fold (CI=0.37) (P<0.001). FUC significantly increased the accumulation of DOX more than verapamil in resistant cells by 2.70, 2.67, and 3.95-fold of untreated cells (p<0.001), respectively. A FUC and DOX combination significantly increased the Rho123 accumulation higher than individual drugs by 2.36-, 2.38-, 1.89-fold verapamil effects in tested cells (p<0.001), respectively. The combination of the FUC and DOX decreased ABCC1, ABCG2, and ABCB1 expression. The FUC and DOX combination increased the levels and activity of caspases (CASP3, CASP8) and p53, while decreased the levels and activity of CYP3A4, GST, and PXR in resistant cancer cells. The combination induced early/late apoptosis to 91.9/5.4% compared with 0.0/0.7% of untreated control. - Conclusion - Our data suggests a new dietary and therapeutic approach of combining the FUC with DOX to overcome multidrug resistance in cancer cells. However, animal experiments should be conducted to confirm the findings before applying the results into clinical trials.